Solubility of Iron, Manganese, and Magnesium Sulfates and Glucoheptonates in Two Alkaline Soils. Issue 3 (24th June 2016) - Shaddox, Travis W.; Unruh, J. Bryan; Kruse, Jason K.; Restuccia, Natasha G.
Abstract : Core Ideas: Iron, Mn, and Mg solubility decreased in as short a time as 1 h. Mg declined only by 10% in 3 wk, but Fe was 93% or more insoluble in 1 h. Glucoheptonate did not increase solubility compared with sulfate in alkaline soils. Sulfate and glucoheptonate forms of Fe, Mn, and Mg are commonly applied to horticultural and agricultural crops. Once these metals enter the soil solution, their solubility may be limited. Glucoheptonate may prolong soil solubility, but its influence in alkaline soils has not been documented. The objective of this study was to determine the solubility of Fe, Mn, and Mg sulfates and glucoheptonates in two alkaline soils. A Tavares sand (a hyperthermic, uncoated Typic Quartzipsamment) and a Fuquay loamy sand (a loamy, kaolinitic, thermic Arenic Plinthic Kandiudult) were incubated with soluble Fe, Mn, or Mg applied as either the sulfate or the glucoheptonate. At 1 h, 4 h, 1 d, and 1, 2, and 3 wk, soils were extracted with 0.01 mol L −1 CaCl2 and analyzed for Fe, Mn, or Mg. At 1 h, approximately 98 and 93% of applied Fe was insoluble in the Tavares sand and Fuquay loamy sand, respectively. The greatest differences between soils occurred with Mn solubility, with 54 and 20% rendered insoluble in Tavares sand and Fuquay loamy sand, respectively, at 1 h. Soluble Mg declined at 1 h by 10%, with no further reductions throughout the 3‐wk incubation. Soil applications of Fe as sulfate or glucoheptonate should be avoided. Applications of Mn sulfate or glucoheptonate may lead to increased soil solubility immediately following the application but may rapidly decline. Magnesium, however, remains soluble for as much as 3 wks. Glucoheptonate did not increase the solubility of Fe, Mn, or Mg compared with sulfate in either soil.